Tranching and rating - Michael Brennan; Julia Hein; Ser-huang Poon (The University of Manchester, Manchester Business School, 2008)
In this paper we analyze the source and magnitude of marketing gains from selling structured debt securities at yields that reflect only their credit ratings, or specifically at yields on equivalently rated corporate bonds. We distinguish between credit ratings that are based on probabilities of default and ratings that are based on expected default losses. We show that subdividing a bond issued against given collateral into subordinated tranches can yield significant profits under the hypothesized pricing system. Increasing the systematic risk or reducing the total risk of the bond collateral increases the profits further. The marketing gain is generally increasing in the number of tranches and decreasing in the rating of the lowest rated tranche.
Keywords: 330; credit ratings; collateralized debt obligations; expected loss rate; default probability; systemic risk; Kreditwürdigkeit; Kreditsicherung; Optionsgeschäft; Credit Default Swap; Hybrides Finanzprodukt; Risikomanagement